Mixed Jacobi-Fourier spectral method for Fisher equation - Jiao, Yujian; Wang, Tianjun; Shi, Xiandong; Liu, Wenjie (Mathematical Modelling and Analysis, 2018)
In this paper, we propose a mixed Jacobi-Fourier spectral method for solving the Fisher equation in a disc. Some mixed Jacobi-Fourier approximation results are established, which play important roles in numerical simulation of various problems deﬁned in a disc. We use the generalized Jacobi approximation to simulate the singularity of solution at the regional center. This also simpliﬁes the theoretical analysis and provides a sparse system. The stability and convergence of the proposed scheme are proved. Numerical results demonstrate the eﬃciency of this new algorithm and coincide well with the theoretical analysis.